THEORETICAL ANALYSIS OF SOLAR WATER HEATING SYSTEM MADE OF NON-METALLIC MATERIALS - Dev, Rahul; Tewari, Kirti; Singh, Dhananjay (MATTER: International Journal of Science and Technology, 2017)
Solar Water heating is a renewable energy based technology. It requires solar radiation received from the sun to heat the water using thermosiphon process. In this paper, a solar water heater (SWH) of capacity 200 L is proposed which is made of non-metallic materials such as fibre reinforced plastic (FRP) and acrylic. A solar photovoltaic panel is also used to generate the electricity which can be used for the forced mode circulation of the water. A thermal model is developed and performance is analyzed for the climatic condition of Allahabad (25.4358° N, 81.8463° E).The result shows that the maximum water temperature in tubes of collector and storage tank for the month of April are 66C respectively. Electrical efficiency and overall efficiency of the system has been found to vary between 10-11% and 20-23% for the month of April, 2016 respectively.